Kebijakan Peraturan Menteri Dalam Negeri Nomor 50 Tahun 2020 Dalam Mengatur Ijin Pelaku Bisnis di E-Commerce Dan Social Commerce (Tiktok Shop) - Sinaga, Lestari Victoria; Sidauruk, Jupenris (Jurnal Ilmiah Penegakan Hukum, 2023)
This research aims to find out the revision of e-commerce import regulations approved by the Indonesian Government through the Minister of Trade Number 50 of 2020 concerning Digital Trade into Minister of Trade Regulation Number 50 of 2023. This research uses normative juridical methods Minister of Home Affairs Regulation Number 31 of 2023 is a revision of Minister of Home Affairs Regulation Number 50 of 2022, several things have been revised. namely: information and standardization of goods, standard information on goods, minimum prices for imported goods, market places are prohibited from being producers, and social commerce is a place for promotions and transactions are prohibited for domestic products. This government policy is the basis for producers being prohibited from selling their products if they want to sell or promote using e-commerce, not e-commerce shopping, so it is clear that this Government Policy is a regulation as a social media organizer that facilitates the promotion of goods and services. The government needs to continue to monitor and evaluate the implementation of this regulation and understand the impact between business actors and the government so that it becomes an effective tool to encourage growth and innovation in the realm of Indonesian digital trade. The contents of Minister of Home Affairs Regulation Number 31 of 2023 concerning the prohibition of Tiktok Shop and other social media only from operating as online shop services are clear.